1991
DOI: 10.1128/mcb.11.2.688-698.1991
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor Access Is Mediated by Accurately Positioned Nucleosomes on the Mouse Mammary Tumor Virus Promoter

Abstract: A fragment of the mouse mammary tumor virus (MMTV) promoter was reconstituted from pure histones into a dinucleosome with uniquely positioned octamer cores. Core boundaries for the in vitro-assembled dinucleosome corresponded to the observed in vivo phasing pattern for long terminal repeat nucleosomes A and B. Nuclear factor 1 (NF1), a constituent of the MMTV transcription initiation complex, was excluded from the assembled dinucleosome, whereas the glucocorticoid receptor was able to bind. During transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…In vivo the protamines, which can contain extensive tracts of polyarginine, accumulate to a large excess during spermatogenesis to achieve this displacement of histones. The energetic considerations involved in the binding of single transcription factor to a specific sequence are likely to be insufficient to disrupt all of the histone-DNA interactions in a complete nucleosome core particle; other mechanisms must mediate nucleosome disruption (Pina et al, 1990;Archer et al, 1991;Perlmann, 1992;Hayes & Wolffe, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo the protamines, which can contain extensive tracts of polyarginine, accumulate to a large excess during spermatogenesis to achieve this displacement of histones. The energetic considerations involved in the binding of single transcription factor to a specific sequence are likely to be insufficient to disrupt all of the histone-DNA interactions in a complete nucleosome core particle; other mechanisms must mediate nucleosome disruption (Pina et al, 1990;Archer et al, 1991;Perlmann, 1992;Hayes & Wolffe, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…11 Although the nucleosome is stable in physiological conditions, it undergoes large-scale structural rearrangements during different cell cycles. DNAbinding proteins such as transcription factors, 12,13 chromatin remodelers, 14 and polymerases 15,16 need to bind nucleosomal DNA. Furthermore, the sequence of nucleosomal DNA may determine the strength of histone−DNA interactions and may encode organization of the nucleosome at larger length scales.…”
Section: Introductionmentioning
confidence: 99%
“…The mouse mammary tumor virus (MMTV) LTR has been well characterized as a steroid-inducible transcription unit (Hager, 1988;Beato, 1989;Gunzburg & Salmons, 1992), and more recently has provided the field of chromatin with an important model for the regulation of transcription by histones [see Hager et al (1993) and references cited therein]. Current understanding of the nucleoprotein structure of the MMTV LTR is based on data obtained by low-resolution mapping of nucleosome positions in vivo (Richard-Foy & Hager, 1987;Bresnick et al, 1991;Truss et al, 1993), and by reconstitution of small fragments of the LTR with histones in vitro (Perlmann & Wrange, 1988;Pina et al, 1990a,c; Archer et al, 1991). The resulting model of LTR chromatin structure incorporates the LTR into an array of six phased nucleosomes (Richard-Foy & Hager, 1987;Perlmann & Wrange, 1988;Pina et al, 1990b).…”
mentioning
confidence: 99%
“…In this context, the B nucleosome region contains four hormone response elements (HREs) and a cognate binding site for the NF-1 transcription factor. The nucleoprotein structure in this region of the LTR is observed to undergo a structural transition that increases the accessibility of DNase I (Richard-Foy & Hager, 1987;Sistare et al, 1987;Bresnick et al, 1990), restriction endonucleases (Bresnick et al, 1991;Archer et al, 1991Archer et al, , 1992Archer et al, , 1994, and MPE-Fe(II) (Richard-Foy , in response to treatment with dexamethasone. Data from several laboratories regarding the in vitro reconstitution of nucleosomes containing B region DNA have suggested that a reconstituted nucleosome adopts a single position on the DNA (Perlmann & Wrange, 1988;Pina et al, 1990b;Archer et al, 1991).…”
mentioning
confidence: 99%